Analysis of News Content: Electability of Edy Rahmayadi vs M. Bobby Afif Nasution in the 2024 North Sumatra Governor Election in Tribunnews.com - Nasution, Deddy Parwis Jailani; Ramadani, Defri; Effendi, Ahmad Yasser (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2025)
Simultaneous regional elections in Indonesia in 2024, including the North Sumatra gubernatorial election on November 27 2024. Online media is a political tool to increase electability which is considered more effective in disseminating information more quickly. This research analyzes news published by Tribunnews regarding the electability of candidate pairs in the 2024 North Sumatra gubernatorial election using qualitative methods, content analysis techniques. The research reveals that news about gubernatorial candidates' electability is objective and balanced, contributing to understanding the relationship between media, politics, and society in the context of the North Sumatra Gubernatorial Election. The study uses two categorizations: trend and direction of issues. The population in this study is electability news from a survey institute for the North Sumatra Gubernatorial Election in Tribunnews media from September to November 2024. The sample required is 24 news stories analyzed by researchers. It can be concluded that the news on the electability of candidate pairs in the 2024 North Sumatra Gubernatorial Election in the Tribunnews media has a tendency with 24 news stories favoring candidate pair number 1 and no news favoring candidate pair number 2 which is directed towards the issue of support for candidate pair number 1. The central role of the editor in the discourse practices in the editorial room is evident, as they can create the direction of the issue and determine the direction of the discourse it constructs.